Isolasi Bakteri Pengakumulasi Poliposfat - I Made Sudiana (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2004)
Polyphosphate accumulating bacteria play  important key role on biological phosphorous removal. Activated sludge originated from wastewater treatment plant for drinking water production acclimated with anaerobic-aerobic phase in sequential batch reactor continuously succeed to establish microbial community that are able to adsorb glucose and acetate under anaerobic condition.  Acinetobacter calcoaceticus S1 was an isolated bacterium from community performing organic substrate absorption. S1 is able to adsorb glucose and acetate under anaerobic condition. During substrate absorption an increase of orthophosphate in bulk solution indicating phosphate released out of cell. Reduction of glycogen and polyhydroxybutirate (PHB) took place under anaerobic phase. S1 is a community member of anaerobic-aerobic system for removal of phosphorous in influent wastewater.